Chromosome-size variation in Giardia lamblia: the role of rDNA repeats. - Adam, R D (1992)
Giardia lamblia trophozoites contain at least five sets of chromosomes that have been categorized by chromosome-specific probes. Pulsed field separations of G. lamblia chromosomes also demonstrated minor bands in some isolates which stained less intensely with ethidium than the major chromosomal bands. Two of the minor bands of the E11 clone of the ISR isolate, MBa and MBb, were similar to each other and to chromosomal band I by hybridization to total chromosomal DNA and by hybridization of specific probes. In order to determine the extent of this similarity, I have developed a panel of probes for many of the Pacl restriction fragments and have shown that most of the Pacl and Notl fragments found in MBa are also present in MBb. The differences are found in both telomeric regions. At one end, MBb contains a 300 kb region not found in MBa. At the other end of MBb is a 160 kb region containing the rDNA repeats which is bounded on one end by the telomeric repeat and on the other by sites for multiple enzymes that do not digest the rDNA repeats. The corresponding region of MBa is 23 kb in size. The size difference is consistent with the eightfold greater number of rDNA repeats in MBb than MBa and suggests that 30% of the size difference is accounted for by different numbers of copies of the rDNA repeat. MBa of another ISR clone (ISR G5) is 150 kb larger in size than MBa of ISR E11. The data suggest that MBa and MBb are homologous chromosomes of different sizes and that a portion of the size difference is accounted for by different copy numbers of the rDNA repeat.